Optimal active defense decision model of wireless communication network under APT attack - Meng MENG; Danni WANG; Jun LYU; Fuliang ZHANG (Dianxin kexue)
The optimal active defense decision can ensure the security and stability of wireless communication networks.In order to improve the defense effectiveness of wireless communication networks, an optimal active defense decision model for wireless communication networks under APT attacks was proposed.Wireless communication network logs were associated, a set of APT attack objects were constructed, the absolute compatibility of APT attack events was calculated through feedback compatibility coefficients, and APT attack behaviors were predicted.Based on the channel bandwidth of APT attack sources on wireless communication networks, the location of the wireless communication network being attacked by APT was obtained, and the weight coefficients of wireless communication network nodes were used to extract the APT attack characteristics of the wireless communication network.Using the attack and defense diagram, the degree of damage caused by APT attacks to wireless communication networks was calculated.By defining the security status of wireless communication networks, an optimal active defense decision model for wireless communication networks was constructed.The experimental results show that the proposed model can increase the packet rejection rate and throughput of attack packets to over 90% and 16 000 bit/s respectively when defending against APT attacks in wireless communication networks, with lower time delay and better defense effectiveness.